Service with a Smile - Ghani, Ejaz; Goswami, Arti Grover; Kharas, Homi (World Bank, Washington, DC, 2014)
Can service be a growth escalator? The world is experiencing its third industrial revolution, and services are at the forefront of this revolution. Services have already surpassed industry as a source of economic growth and job creation, in both developed and developing economies. In the industrial sector, technologies have matured and employment is shrinking. However, services are getting more sophisticated and jobs are expanding. Services growth is also more inclusive and sustainable. It increases the participation of women in the labor force and places a lighter burden on natural resources. The promise of the services revolution is that countries do not need to wait to get started with rapid development. There is a new boat that development latecomers can take.